2019
DOI: 10.3390/ijerph16193675
|View full text |Cite
|
Sign up to set email alerts
|

The Risk Factors Related to Voice Disorder in Teachers: A Systematic Review and Meta-Analysis

Abstract: Background and Objectives: Identifying the risk factors of teachers’ voice disorders is very important for preventing voice disorders and the recurrence of them. This meta-study identified risk factors associated with teachers’ voice disorders through systematic review and meta-analysis and provided basic data for preventing them. Materials and Methods: This study collected literature on the risk factors of teachers’ voice disorders using six databases (i.e., CINAHL, EBSCO, PUBMED, SCOPUS, Web of Science, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
54
0
9

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(72 citation statements)
references
References 40 publications
9
54
0
9
Order By: Relevance
“…In contrast, age, number of students in class, consumption of alcoholic beverages, physical activity, smoking, water consumption, singing habits, duration of teaching, perception of noise inside the school, number of classes per day, evaluation of noise inside the classroom, and perception of technology and instruments inside the workplace were not related to the presence of voice disorders. However, the author encourages further research to estimate the risk factors for voice disorders in teachers based on the results yielded ( 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, age, number of students in class, consumption of alcoholic beverages, physical activity, smoking, water consumption, singing habits, duration of teaching, perception of noise inside the school, number of classes per day, evaluation of noise inside the classroom, and perception of technology and instruments inside the workplace were not related to the presence of voice disorders. However, the author encourages further research to estimate the risk factors for voice disorders in teachers based on the results yielded ( 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…The quality of study reporting in the included studies was appraised using the 14‐item Standard Quality Assessment Criteria for Evaluating Primary Research Papers from a Variety of Fields developed by Kmet et al 8 This quality assessment tool has previously been used for critical appraisal of studies in systematic reviews of observational studies 9 and randomised controlled trials 10 . The items used for assessing the quality of the studies are listed in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…5 Psychological stress appears to be one of the most important risk factors for the development of vocal symptoms for teachers even when compared with factors such as voice load (eg, number of teaching years, number of students in the classroom) or environmental issues such as classroom acoustics. 6,7 Although numerous studies have investigated and identified risk factors that may lead to voice disorders in school teachers (for a systematic review and meta-analysis see Byeon 8 ), little is known about risk factors relating to voice disorders among university teaching faculty, who teach under comparable (eg, talking for long periods of time, teaching in environments with background noise, and often increasing their volume) as well as unique circumstances (eg, teaching large audiences). 9 Higgins 9 reported that 45% of the university teaching faculty surveyed stated having a voice disorder and Korn, Pontes, Abranches, and Pontes 10 stated that 39.6% of the university professors surveyed reported hoarseness.…”
Section: Introductionmentioning
confidence: 99%